EVALUASI SEDIAAN MASKER GEL PEEL-OFF KOMBINASI EKSTRAK DAUN MANGGA BACANG (Mangifera foetida)DAN DAUN SALAM (Syzygium polyanthum) - Putriani, Kony; Mardhiyani, Dini; Anggraini, Lovera (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2022)
Mango Bacang leaves and bay leaves are plants that can be used as ingredients in traditional medicine as natural antibacterials which are believed to help get rid of acne. Several previous studies also reported that Bacang mango leaves and bay leaves have activity against Staphylococcus aureus, Escherichia coli and Salmonella typhi bacteria. This study aims to determine the evaluation results of peel-off gel mask preparations that meet the requirements. The test methods include organoleptic test, pH test, viscosity, homogeneity test and dispersion test. The test results showed that F1 and F2 were the best formulas with the characteristics of a green-black gel, a characteristic odor of mango Bacang and bay leaves, a viscosity of 1129 cPs and 1135 cPs, pH 4.4 and 4.5. The dispersion test was 5.1 cm and 5.7 cm and the homogeneity test on the peel off gel mask was homogeneous, there were no fibers, lumps or differences in color when applied to a transparent slide.